2016
DOI: 10.1073/pnas.1606791113
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and genetic factors support the dissociation between α-synuclein aggregation and toxicity

Abstract: Synucleinopathies are a group of progressive disorders characterized by the abnormal aggregation and accumulation of α-synuclein (aSyn), an abundant neuronal protein that can adopt different conformations and biological properties. Recently, aSyn pathology was shown to spread between neurons in a prion-like manner. Proteins like aSyn that exhibit self-propagating capacity appear to be able to adopt different stable conformational states, known as protein strains, which can be modulated both by environmental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 74 publications
2
61
1
Order By: Relevance
“…The capacity of copper to bind to alpha-synuclein at H50 could also be highly relevant for disease pathology in humans. Indeed, the point mutation H50Q which leads to a familial form of PD corresponds to the major copper(II) binding site (Proukakis et al, 2013) and binding of copper(II) to this mutant results in a structurally different species compared to the copper-WT species (Villar-Piqué et al, 2016). The ability of copper to accept or donate electrons implicates it in the production of ROS in PD (Barnham et al, 2004; Barnham and Bush, 2008; Valensin et al, 2016), and it has more recently been shown that in the SN, total tissue copper is decreased (Montes et al, 2014).…”
Section: Copper and α-Synuclein Diseasementioning
confidence: 99%
“…The capacity of copper to bind to alpha-synuclein at H50 could also be highly relevant for disease pathology in humans. Indeed, the point mutation H50Q which leads to a familial form of PD corresponds to the major copper(II) binding site (Proukakis et al, 2013) and binding of copper(II) to this mutant results in a structurally different species compared to the copper-WT species (Villar-Piqué et al, 2016). The ability of copper to accept or donate electrons implicates it in the production of ROS in PD (Barnham et al, 2004; Barnham and Bush, 2008; Valensin et al, 2016), and it has more recently been shown that in the SN, total tissue copper is decreased (Montes et al, 2014).…”
Section: Copper and α-Synuclein Diseasementioning
confidence: 99%
“…Studies indicate that Cu accumulates in specific brain regions of aged subjects (Braidy et al., ; Fu, Jiang, & Zheng, ; Pushkar et al., ; Singh et al., ; Wang, Becker, et al., ; Zatta et al., ). In neurodegenerative diseases, long‐term Cu dyshomeostasis plays a role in oxidative damage, and redox‐active Cu accelerates formation of toxic oligomers associated with some neurodegenerative factors (e.g., Amyloid β, alpha synuclein) (Ahuja, Dev, Tanwar, Selwal, & Tyagi, ; Dell'Acqua et al., ; Greenough et al., ; Kawahara et al., ; Lan, Chen, Chai, & Hu, ; Okita et al., ; Squitti, ; Villar‐Pique et al., ). Thus, some circadian abnormalities observed in aged subjects and those with neurological diseases may involve Cu dyshomeostasis, an idea that warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…We still do not understand in detail what are the cellular factors that affect aSyn aggregation and cytotoxicity. The current hypothesis suggests that, during the process of aSyn assembly, soluble and cytotoxic oligomers may form and cause cell dysfunction and death (Conway et al, ; Outeiro et al, ; Villar‐Pique et al, ).…”
Section: Cell Models Of Asyn Toxicity and Aggregationmentioning
confidence: 99%